1996
DOI: 10.1046/j.1471-4159.1996.67010251.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases in the Neocortex and Spinal Cord of Amyotrophic Lateral Sclerosis Patients

Abstract: Matrix metalloproteinases (MMPs) were analyzed by immunohistochemistry and zymography in amyotrophic lateral sclerosis (ALS) and control brain and spinal cord specimens. Three major bands of enzyme activity (70, 100, and 130 kDa) were consistently observed and were subsequently identified as MMP-2 (70 kDa; also known as EC 3.4.24.24 or gelatinase A) and MMP-9 (100 and 130 kDa; also known as EC 3.4.24.35 or gelatinase B). Immunohistochemical studies established the presence of MMP-2 in astrocytes and MMP-9 in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(75 citation statements)
references
References 22 publications
6
68
1
Order By: Relevance
“…A number of reports have indicated that MMPs are involved in the pathogenesis of a wide range of diseases and disorders of the CNS, including neurodegenerative diseases such as Alzheimer's disease, amyotrophic lateral sclerosis, Parkinson's disease and progressive supranuclear cerebral palsy [10][11][12][13][14] as well as stroke injuries [15]. It has been suggested that this class of extracellular proteases may be appropriate molecular targets to reduce secondary tissue degeneration and improve functional outcome [7,16].…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have indicated that MMPs are involved in the pathogenesis of a wide range of diseases and disorders of the CNS, including neurodegenerative diseases such as Alzheimer's disease, amyotrophic lateral sclerosis, Parkinson's disease and progressive supranuclear cerebral palsy [10][11][12][13][14] as well as stroke injuries [15]. It has been suggested that this class of extracellular proteases may be appropriate molecular targets to reduce secondary tissue degeneration and improve functional outcome [7,16].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that past results have been inconsistent with respect to the cellular localization of MMPs in the brain (Del-Bigio and Jacque, 1995;Backstrom et al, 1996;Gottschall and Deb, 1996;Lim et al, 1996;Romanic et al, 1998), we first investigated the tissue distribution of MMPs within the rat forebrain by means of in situ hybridization and immunocytochemistry. Coronal sections of 2-month old rat brains were analyzed at the level of the dorsal hippocampus (Fig.…”
Section: Mmp-9 and Mmp-2 Are Differentially Distributed In The Adult mentioning
confidence: 99%
“…This notion appears surprising in the context of the previously described data implicating MMP-9 in neuronal plasticity. However, although under the variety of neurodegenerative conditions (ischemia, brain trauma, viral infections, amyotrophic lateral sclerosis, ALS, Parkinson's disease, PD, Alzheimer's disease, AD) MMP-9 still remains mainly neuronal in origin, it is not clear whether it is expressed by the neurons prone to death and/or those attempting to recover from the damage [12,20,31,32,43,[57][58][59]. As it has recently been pointed out that both possibilities should be equally considered [60].…”
Section: Mmps In the Brainmentioning
confidence: 99%